Fuzzy Modeling of Salinity Effects on Radish Yield Under Reuse Water Irrigation - Putti, Fernando F. [UNESP]; Cremasco, Camila P. [UNESP]; Junior, Josué F. Silva; Filho, Luís R. A. Gabriel [UNESP] (FapUNIFESP (SciELO), 2022)
The increase of water usage for food production in recent years has triggered researches on ways to optimize the use of water and to reuse saline water. The present study analyzes the effects of reused saline water in the irrigation of radish culture and the construction of a fuzzy logical mathematic model so that producers may evaluate their production. The experiment, measuring the development of radish bulb at five saline water levels, was developed in a greenhouse in the Botucatu, Campus of the São Paulo State University (UNESP), Botucatu/SP, Brazil. Results showed that salinity caused reduction in fresh and dry matter of the bulb and affected ratings throughout the culture cycle. From the developed fuzzy model, it was possible to verify that the fuzzy modeling helps in the analysis of the experimental data and makes it possible to perform simulations capable of inferring points that were not experimentally determined.
Keywords: Artificial intelligence; Optimization; Saline water